Saberes da experiência mobilizados durante a prática da docência por professores de Educação Física - Brandt, Léocla Vanessa (2019)
Teachers in the course of their teaching have been asked quite a lot about what knowledge they need to know for the teaching of their students. Especially in the area of Physical Education, teachers often suffer questions for using knowledge that is acquired through their experience. It is believed that the knowledge mobilized by teachers is of great relevance in the school environment, as it mobilizes a vast repertoire of knowledge proper to teaching. Thus, this work had as its theme the teaching knowledge mobilized during the teaching practice by PE teachers, aiming to understand how the professional career of PE teachers enables the construction of the experiential knowledge mobilized by them in the processes of organization and development of the teaching process. teaching. In this context, we have as research problem: which elements are integrated in the knowledge of the experience mobilized by them in the processes of organization and development of teaching. As research questions we have: 1- How was the process of constitution of teaching for basic education; 2 - how PE teachers justify the activities performed in the organization and development of teaching; 3- what is the origin of the experiential knowledge mobilized by teachers in the process of organization and development of teaching; and 4- how the school context conditions the activities performed by teachers in the organization and development of teaching. In the search for these answers, a qualitative research was chosen as the path. The data treatment was based on the content analysis of the statements collected during the interviews of the 3 (three) public school teachers of a state school in the city of Santa Maria - RS. During the analysis of the teachers data, it was noticed that in relation to the construction of knowledge, we can say that: the knowledge is built during the professional career through the influence of the courses and the experience in which the teachers had before their formation and during professional experiences, enabling the construction, re-elaboration and validation of new knowledge necessary for teaching. Based on the analysis of the information collected, we conclude that the professional career of teachers enables the construction of experiential knowledge through the different contexts to which teachers are inserted.